RELIGIOUS LEADER AND CHARISMATIC LEADERSHIP IN INDONESIA:THE ROLE OF KYAI IN PESANTREN IN JAVA - Siregar, Ferry Muhammadsyah (Jurnal Kawistara, 2013)
This paper discusses on the role of the kyai in pesantren in Java. It addresses on the roles of religiousleader in pesantren. It applies Max Weberâs concept on religious leadership and charisma. It usesqualitative data for analysis of materials collected from observations and library research. This researchônds that the structures and patterns of leadership and power of Kyai within pesantren are strong inwhich kyai is positioned as the main ôgure. It can be seen on how a kyai build his strategic role as thenon-formal leader in society through intensive communication with the people. The charisma of a kyaialso gains peopleâs support, to some extents, caused by his moral stability and faith quality. This processat ôrst starts from the nearest group around the pesantren and then spread out to distant places.